2002
DOI: 10.3748/wjg.v8.i2.375
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin, somatostatin, G and D cells of gastric ulcer in rats

Abstract: In gastric ulcer, the increased gastrin secreted by G cells, the declined somatostatin secreted by D cells, and the disordered G/D cell ratio can lead to gastrointestinal dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 54 publications
0
22
0
1
Order By: Relevance
“…It was reported that the disordered ratio of G/D cells, which can secrete gastrointestinal hormones gastrin and somatostatin, could lead to gastrointestinal dysfunction in acetic acid induced gastric ulcer model [29] . Maybe BPC 157 can antagonize the agents induced damage by modulating the number of G and D cells and maintaining the stable circumstances of stomach.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the disordered ratio of G/D cells, which can secrete gastrointestinal hormones gastrin and somatostatin, could lead to gastrointestinal dysfunction in acetic acid induced gastric ulcer model [29] . Maybe BPC 157 can antagonize the agents induced damage by modulating the number of G and D cells and maintaining the stable circumstances of stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Eeubi indicated that the persistent absence of somatostatin receptrors for several months after ulceration might be of pathophysiological significance for ulcer healing. Sun et al 126) examined plasma gastrin and somatostatin levels, as well as the number of G and D cells in the antrum and the G/D ratio, in rats with acetic acid ulcers. Sun found increased gastrin levels and G/D ratios, as well as decreased somatostatin levels after ulceration; nonetheless, such changes gradually returned to normal as healing progressed.…”
Section: Hormonesmentioning
confidence: 99%
“…Somatostatin, an important peptide for inhibiting cellular proliferation and differentiation, could slow down the growth of various kinds of cells by blocking the synthesis and/or secretion of many important cytokines and hormones [10][11][12][13][14] . On the other hand, extensive physiological effects of somatostatin and its analogues are mainly mediated by five subtypes of somatostatin receptors (SSTR), including SSTR 1 , SSTR 2 (SSTR 2a and SSTR 2b ), SSTR 3 , SSTR 4 and SSTR 5 .…”
Section: Discussionmentioning
confidence: 99%